A comprehensive approach to complementary and alternative medicine usage among patients from a vascular department. (April 2022) - Cuen-Ojeda, Cesar; Hinojosa, Carlos A; Contreras-Yáñez, Irazú; Elenes-Sánchez, Erika; Rosas-Ríos, Casandra; Méndez-Sosa, Miguel A; Ballinas-Sánchez, Angel; Pascual-Ramos, Virginia
Introduction: Use of complementary and alternative medicine (CAM) therapies had been described in patients with disabling, chronic and painful conditions; these characteristics define the majority of vascular surgery (VS) entities. A lack of disclosure about CAM use from patients has been universally cited and may impact effective patient–doctor communication. Our primary objective was to describe CAM use, modalities, perceived benefits, safety, and associated factors among adult patients attending a VS outpatient clinic; we additionally explored patient's attitudes about CAM disclosure with their primary vascular surgeon. Methods: This cross-sectional study invited 223 consecutive outpatients to an interview where the ICAM-Q (International Complementary and Alternative Medicine Questionnaire) and the PDRQ-9 (Patient-Doctor Relationship Questionnaire-9 items) were applied. In addition, sociodemographics, vascular disease and treatment-related information, comorbidity, and disease severity characteristics were obtained. Appropriated statistics was used; multiple logistic regression analysis identified factors associated to CAM use. All statistical tests were two-sided, and a p value ≤ 0.05 was considered significant. IRB approval was obtained. Results: Patients recruited were primary females (69%) and had a median age of 65 years (54–75). Most frequent vascular diagnoses were chronic venous insufficiency (36.2%) and peripheral artery disease (26%). There were 104 (46.6%) patients who referred CAM use, primarily self-helped practices (96%), and use of herbal, vitamins, or homeopathic medicines (23.7%). Overall, the majority of the patients perceived CAM modalities helpful and 94.6% denied any adverse event. Female sex (OR: 1.768, 95% CI: 0.997–3.135, p  = 0.051) and hospitalization during the previous year (OR: 3.173, 95% CI: 1.492–6.748, p  = 0.003) were associated to CAM use. The majority of the patients (77%) agreed about CAM disclosure with their primary vascular surgeon; meanwhile, among CAM users, up to 54.9% did not disclose it, and their main reasons were "Doctor didn't ask" (32%) and "I consider it unnecessary" (16%). The patient–doctor relationship was rated by the patients with high scores. Conclusions: CAM use is frequent and perceived as safe and beneficial among VS outpatients; nonetheless, patients do not disclose CAM use with their primary vascular surgeons, and a wide range of reasons are given by the patients that prevent effective and open communication.